The Effect of Gainesville’s Urban Trees on Energy Use of Residential Buildings - Francisco Escobedo; Jennifer A. Seitz; Wayne Zipperer (EDIS, 2012)
Based on a 2007 average retail price of electricity in Florida, trees in Gainesville are estimated to provide about $1.9 million in savings each year due to reduced air conditioning and heating use. However, trees also increase energy costs in winter by approximately $367 thousand annually because their shade cools buildings and thus raises building heating costs. This revised 3-page fact sheet was written by Francisco Escobedo, Jennifer A. Seitz, and Wayne Zipperer, and published by the UF Department of School of Forest Resources and Conservation, February 2012.